Éducation nutritionnelle et acculturation scientifique : quelles circulations de normes et de savoirs dans les discours adressés aux jeunes ? - Denise Orange Ravachol; Susan Kovacs; Christian Orange (Éducation et Socialisation)
In today’s society we find multiple discourses concerning nutrition education, emanating not only from institutions but also from various organizations and entities. While all of these discourses highlight the individual’s capacity to control his own behavior, certain of these discourses are implicitly contradictory. Our article explores the hybrid and indeterminate nature of problems surrounding nutrition education. Using a dual approach combining didactics and information-communication science, we base our analysis on the fundamental distinction between problematization, a condition for the treatment scientific issues, and the appeal to unquestioned self-evident truths, typical of the treatment of everyday issues. We examine the circulation of norms and knowledge within various types of discourses directed at youngsters, in both informal (supermarket nutritional brochures) and formal contexts (institutional recommendations, pedagogical resources, school textbooks; ordinary teaching sequences). We show that norms and knowledge circulate in a polyphonic way, thus blurring the boundaries between discursive positions, and contributing to the promotion of ready-made solutions legitimized through references to “medical expertise.” In order to confer significant critical and argumentative depth to nutrition education, it is necessary to develop scientific training and pedagogy which emphasize the value of problematization.